Polyester film as well as preparation method and application thereof
By using polyester films prepared with ether-containing glycol, ether-containing diacid and nano-ferrous tetraoxide in lithium-ion batteries, the bonding force between the composite fluid and the metal plating is improved, and the problem of delamination of the base film and the plating layer is solved. Improves the stability and energy density of lithium-ion batteries.
Patent Information
- Application Number
- CN202411539681.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-31
- Publication Date
- 2025-01-03
AI Technical Summary
The bonding force between the base film and the metal coating in the existing composite current collector is poor, resulting in delamination in high-temperature electrolyte, affecting the stability and safety of lithium-ion batteries.
The composite set is prepared by using ether-containing glycol, ether-containing diacid and nano-ferrous tetraoxide as raw materials for the preparation of polyester films. The polyester film and metal plating are improved by introducing polar groups and increasing surface roughness, and the combined force of the polyester film and metal plating are prepared. Fluids are used to replace traditional pure aluminum current collectors.
It effectively improves the stability of the composite current collector in the working environment of lithium-ion batteries, reduces the current collector density, improves the energy density and safety performance, and avoids delamination.
Smart Images

Figure CN119241822A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of composite current collectors for lithium ion batteries and relates to a polyester film and a preparation method and application thereof. Background Art
[0002] In recent years, lithium-ion batteries have stood out among a number of energy storage technologies due to their safety, low cost, convenience and other advantages, and have been widely used in new energy vehicles, new energy motorcycles, large-scale energy storage, smart phones, virtual reality displays and other commercial and civilian fields. Due to the continuous upgrading of the new energy industry, higher requirements have been put forward for the energy density and safety of lithium-ion batteries.
[0003] A typical lithium-ion battery consists of a positive electrode, a negative electrode, a separator, an electrolyte and a current collector. The current collector is one of the indispensable components of a lithium-ion battery. On the one hand, it bears the role of carrying active materials. On the other hand, it serves as a carrier for the electron transmission of positive and negative electrode materials and plays a role in establishing the current transmission path of the internal and external circuits. At present, copper foil is usually used as the negative electrode current collector and aluminum foil is used as the positive electrode current collector. This metal foil current collector accounts for about 15-20wt% of the total weight of the lithium-ion battery. It does not contribute to the battery capacity during the battery charging and discharging process and is an inactive component in the battery. At present, how to achieve lightweight current collectors and reduce the amount of inactive components to increase energy density has become a key issue in the development of high-performance lithium-ion batteries.
[0004] Among them, composite current collectors can not only reduce weight and improve energy density, but also ensure the safety of lithium-ion batteries during use, while also taking cost into account, and are most likely to replace traditional pure metal current collectors.
[0005] However, the bonding force between the base film (such as PET, etc.) and the metal coating in the current composite collector is currently poor, which will cause delamination of the current composite collector when immersed in a high-temperature electrolyte, thereby affecting the use of the battery.
[0006] Therefore, in the art, it is desired to develop a base film for a current collector that has good bonding strength with a metal plating layer. Summary of the invention
[0007] In view of the shortcomings of the prior art, the purpose of the present invention is to provide a polyester film and a preparation method and application thereof. Compared with the traditional pure aluminum current collector, the composite current collector made of the polyester film provided by the present invention has a lower density, thereby improving the battery energy density, and solves the problem that the aluminum layer in the composite current collector is easily separated from the PET base film.
[0008] In order to achieve the purpose of the invention, the present invention adopts the following technical solutions:
[0009] In a first aspect, the present invention provides a polyester film, wherein the raw materials for preparing the polyester film include the following components in parts by weight:
[0010]
[0011] The raw materials for preparing the polyester film provided by the present invention include ether diol, ether diacid and nano-ferrosilicate. The synergistic effect of the three makes the prepared polyester film have higher surface energy and roughness. The use of the composite current collector can solve the problem of poor bonding between the base film and the metal coating, effectively improve the stability of the composite current collector in the working environment of the lithium ion battery, and improve the safety of the lithium ion battery.
[0012] The present invention introduces polar groups into polyester chain segments to increase the surface energy of the film, which is beneficial to chemical aluminum plating; nano magnetic substances are added during the synthesis process and enriched on the surface of the film, which increases the roughness of the surface and is more beneficial to improving the bonding force between the film and the metal coating; the problem of poor bonding force between the base film and the metal coating is solved from two aspects of the body and the additive.
[0013] In the present invention, the raw materials for preparing the polyester film are calculated by weight. Taking 100 parts of terephthalic acid as the basis, the amount of ethylene glycol can be 45 parts, 46 parts, 47 parts, 48 parts, 49 parts, 50 parts, 51 parts, 52 parts, 53 parts, 54 parts, 55 parts, etc.; the amount of ether diol can be 1 part, 1.2 parts, 1.4 parts, 1.6 parts, 1.8 parts, 2 parts, 2.2 parts, 2.4 parts, 2.6 parts, 2.8 parts, 3 parts, etc.; the amount of ether diol can be 1 part, 1.2 parts, 1.4 parts, 1.6 parts, 1.8 parts, 2 parts, 2.2 parts, 2.4 parts, 2.6 parts, 2.8 parts, 3 parts, etc. The dosage can be 1 part, 1.2 parts, 1.4 parts, 1.6 parts, 1.8 parts, 2 parts, 2.2 parts, 2.4 parts, 2.6 parts, 2.8 parts, 3 parts, etc.; the dosage of the catalyst can be 0.02 parts, 0.025 parts, 0.03 parts, 0.035 parts, 0.04 parts, etc.; the dosage of nano-ferroferric oxide can be 3 parts, 3.2 parts, 3.4 parts, 3.6 parts, 3.8 parts, 4 parts, 4.2 parts, 4.4 parts, 4.6 parts, 4.8 parts, 5 parts, etc.
[0014] Preferably, the ether-containing diol contains at least one ether bond.
[0015] Preferably, both ends of the molecular chain of the ether-containing diol are carbon hydroxyl groups.
[0016] Preferably, the ether-containing diol comprises polyether diol and / or 2,5-tetrahydrofuran dimethanol.
[0017] Preferably, the polyether diol includes polytetrahydrofuran, for example, the brand name may be P141386 or the like.
[0018] Preferably, the ether-containing diacid contains at least one ether bond.
[0019] Preferably, the two ends of the molecular chain of the ether-containing diacid are carboxyl groups.
[0020] Preferably, the ether-containing diacid comprises 2,5-furandicarboxylic acid.
[0021] Preferably, the catalyst comprises antimony glycolate.
[0022] Preferably, the particle size of the nano-ferroferric oxide is not greater than 200 nm, for example, 200 nm, 180 nm, 150 nm, 130 nm, 100 nm, 50 nm, etc.
[0023] In a second aspect, the present invention provides a method for preparing the polyester film as described in the first aspect, the preparation method comprising the following steps:
[0024] (1) Adding the formulated amount of terephthalic acid, ethylene glycol, ether-containing glycol, ether-containing diacid, catalyst, and nano-ferrosoferric oxide into a reaction kettle, and exhausting nitrogen to remove all air;
[0025] (2) adding nitrogen until the pressure in the reactor reaches 90 to 150 kPa (e.g., 90 kPa, 100 kPa, 120 kPa, 130 kPa, 150 kPa, etc.);
[0026] (3) stirring and rapidly heating to 210-230° C. (e.g., 210° C., 215° C., 220° C., 225° C., 230° C., etc.), and the pressure reaches 340-360 kPa (e.g., 340 kPa, 345 kPa, 350 kPa, 355 kPa, 360 kPa, etc.);
[0027] (4) maintaining stirring to start the esterification reaction and release the pressure, reducing the pressure to 0 kPa within 110 to 130 minutes (e.g., 110 minutes, 115 minutes, 120 minutes, 125 minutes, 130 minutes, etc.);
[0028] (5) Under nitrogen atmosphere, stirring and heating to 270-290° C. (e.g., 270° C., 275° C., 280° C., 285° C., 290° C., etc.);
[0029] (6) using a vacuum pump to bring the pressure in the reactor to -110 to -90 kPa (e.g., -110 kPa, -100 kPa, -90 kPa, etc.) within 50 to 70 min (e.g., 50 min, 55 min, 60 min, 65 min, 70 min, etc.);
[0030] (7) maintaining the vacuum degree until the intrinsic viscosity of the product at the end of the polycondensation is ≥0.7 dL / g (e.g., 0.7 dL / g, 0.8 dL / g, 0.9 dL / g, etc.), keeping the heating off, stirring, introducing nitrogen to press out the product, and letting the product flow into pure water for drawing to obtain a strand;
[0031] (8) pelletizing and drying the strands, and then biaxially stretching them to form a film;
[0032] (9) The film is passed through a high-intensity magnetic field and then cooled to obtain the polyester film.
[0033] Preferably, the temperature of the pure water in step (7) is 8-12°C, for example, 8°C, 9°C, 10°C, 11°C, 12°C, etc.
[0034] Preferably, the thickness of the film in step (8) is 3 to 10 microns, for example, 3 microns, 4 microns, 5 microns, 6 microns, 7 microns, 8 microns, 9 microns, 10 microns, etc.
[0035] Preferably, the intensity of the high-intensity magnetic field in step (9) is 0.8-1.2 T, for example, 0.8 T, 0.9 T, 1 T, 1.1 T, 1.2 T, etc.
[0036] Preferably, the temperature of the high-intensity magnetic field in step (9) is 40-60°C, for example, 40°C, 45°C, 50°C, 55°C, 60°C, etc., and the time of passing through the high-intensity magnetic field is 3-8 min, for example, 3 min, 4 min, 5 min, 6 min, 7 min, 8 min, etc.
[0037] In a third aspect, the present invention provides a composite current collector, comprising a base film and aluminum layers disposed on both sides of the base film, wherein the base film comprises the polyester film as described in the first aspect.
[0038] Preferably, the thickness of the aluminum layer (single-sided aluminum layer) is 0.5-1.5 microns, for example, 0.5 microns, 0.6 microns, 0.8 microns, 1 micron, 1.2 microns, 1.3 microns, 1.5 microns, etc.
[0039] The polyester film provided by the present invention is used for a composite current collector, which solves the problem of poor bonding between the PET base film and the metal coating in the composite current collector, so that the composite current collector can be immersed in an electrolyte in a high temperature environment without delamination and maintain good stability. At the same time, the weight of the current collector is reduced, the battery energy density is improved, and the current collector can be fully applicable to the field of lithium-ion batteries.
[0040] The present invention uses a composite current collector to replace a pure aluminum current collector, thereby reducing density, increasing energy density, and improving the performance of the lithium ion battery.
[0041] In a fourth aspect, the present invention provides a method for preparing the composite current collector as described in the third aspect, the preparation method comprising the following steps:
[0042] The polyester film is placed in a chemical aluminum plating solution, aluminum ions are reduced through redox reaction and deposited on the surfaces of both sides of the polyester film, and then aluminum is plated through vacuum evaporation to obtain the composite current collector.
[0043] Compared with the prior art, the present invention has the following beneficial effects:
[0044] The raw materials for preparing the polyester film provided by the present invention include ether diol, ether diacid and nano-ferrosilicate. The synergistic effect of the three makes the prepared polyester film have higher surface energy and roughness. The use of the composite current collector can solve the problem of poor bonding between the base film and the metal coating, effectively improve the stability of the composite current collector in the working environment of the lithium ion battery, and improve the safety of the lithium ion battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0045] Figure 1 This is a schematic diagram of the molecular structure of the polyester film provided in Example 6.
[0046] Figure 2 A schematic diagram of the structure of the composite current collector provided by the present invention;
[0047] Among them, 1-polyester film, 2-aluminum layer, 3-nano-ferrosilicate. DETAILED DESCRIPTION
[0048] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.
[0049] Unless otherwise specified, some of the raw material information used in the examples and comparative examples of the present invention is as follows:
[0050] Polyether diol: polytetrahydrofuran, molecular weight 850, brand P141386;
[0051] Nano-iron tetroxide: The average particle size is 120nm.
[0052] Example 1
[0053] In this embodiment, a polyester film is provided. The raw materials for preparing the polyester film include the following components in parts by weight: 100 parts of terephthalic acid, 50 parts of ethylene glycol, 1 part of polyether glycol, 1 part of 2,5-furandicarboxylic acid, 0.02 parts of ethylene glycol antimony, and 3 parts of nano-ferrosoferric oxide.
[0054] The preparation method comprises the following steps:
[0055] The above-mentioned raw materials are added to a polyester special reactor, and nitrogen is vented three times to remove air; nitrogen is added until the pressure in the reactor reaches 120 kPa; stirring and rapidly heating to 220°C and the pressure reaches 350 kPa; stirring is maintained to start the esterification reaction and the pressure is slowly released, and the pressure is reduced to 0 kPa within 120 minutes; under the protection of a nitrogen atmosphere, stirring and rapidly heating to 280°C; a vacuum pump is used to make the pressure in the reactor reach -100 kPa within 60 minutes; the vacuum degree is maintained until the intrinsic viscosity at the end of the polycondensation is ≥0.7 dL / g, the heating is kept turned off and stirring is maintained, nitrogen is introduced to press out the product, and the product flows into 10°C pure water for drawing; the wire material is granulated and dried, and a film with a thickness of 4 microns is made by biaxial stretching, and a high-intensity magnetic field (magnetic field strength is 0.8 T) is passed for 5 minutes at 50°C, and then cooled with ice water to obtain the polyester film.
[0056] Example 2
[0057] In this embodiment, a polyester film is provided. The raw materials for preparing the polyester film include the following components in parts by weight: 100 parts of terephthalic acid, 50 parts of ethylene glycol, 1 part of 2,5-tetrahydrofuran dimethanol, 1 part of 2,5-furan dicarboxylic acid, 0.02 parts of ethylene glycol antimony, and 3 parts of nano-ferrosoferric oxide.
[0058] The preparation method comprises the following steps:
[0059] The above-mentioned raw materials are added to a polyester special reactor, and nitrogen is vented three times to remove air; nitrogen is added until the pressure in the reactor reaches 90 kPa; stirring and rapidly heating to 210°C and the pressure reaches 340 kPa; stirring is maintained to start the esterification reaction and the pressure is slowly released to reduce the pressure to 0 kPa within 110 minutes; under the protection of a nitrogen atmosphere, stirring and rapidly heating to 270°C; a vacuum pump is used to make the pressure in the reactor reach -110 kPa within 50 minutes; the vacuum degree is maintained until the intrinsic viscosity at the end of the polycondensation is ≥0.7 dL / g, the heating is kept turned off and stirring is maintained, nitrogen is introduced to press out the product, and the product flows into 8°C pure water for drawing; the wire material is granulated and dried, and a film with a thickness of 4 microns is made by biaxial stretching, and a high-intensity magnetic field (magnetic field strength is 1 T) is passed for 3 minutes at 40°C, and then cooled with ice water to obtain the polyester film.
[0060] Example 3
[0061] In this embodiment, a polyester film is provided. The raw materials for preparing the polyester film include the following components in parts by weight: 100 parts of terephthalic acid, 50 parts of ethylene glycol, 3 parts of polyether glycol, 3 parts of 2,5-furandicarboxylic acid, 0.04 parts of ethylene glycol antimony, and 5 parts of nano-ferrosoferric oxide.
[0062] The preparation method comprises the following steps:
[0063] The above-mentioned raw materials are added to a polyester special reactor, and nitrogen is vented three times to remove air; nitrogen is added until the pressure in the reactor reaches 150 kPa; stirring and rapidly heating to 230°C and the pressure reaches 360 kPa; stirring is maintained to start the esterification reaction and the pressure is slowly released, and the pressure is reduced to 0 kPa within 130 minutes; under the protection of a nitrogen atmosphere, stirring and rapidly heating to 290°C; a vacuum pump is used to make the pressure in the reactor reach -90 kPa within 70 minutes; the vacuum degree is maintained until the intrinsic viscosity at the end of the polycondensation is ≥0.7 dL / g, the heating is kept turned off and stirring is maintained, nitrogen is introduced to press out the product, and the product flows into 12°C pure water for drawing; the wire material is granulated and dried, and a film with a thickness of 4 microns is made by biaxial stretching, and a high-intensity magnetic field (magnetic field strength is 1.2 T) is passed at 60°C for 6 minutes, and then cooled with ice water to obtain the polyester film.
[0064] Example 4
[0065] In this embodiment, a polyester film is provided. The raw materials for preparing the polyester film include the following components in parts by weight: 100 parts of terephthalic acid, 50 parts of ethylene glycol, 3 parts of 2,5-tetrahydrofuran dimethanol, 3 parts of 2,5-furan dicarboxylic acid, 0.04 parts of ethylene glycol antimony, and 5 parts of nano-ferrosoferric oxide.
[0066] The preparation method is as in Example 1.
[0067] Example 5
[0068] In this embodiment, a polyester film is provided. The raw materials for preparing the polyester film include the following components in parts by weight: 100 parts of terephthalic acid, 50 parts of ethylene glycol, 1 part of polyether glycol, 1 part of 2,5-tetrahydrofuran dimethanol, 2 parts of 2,5-furandicarboxylic acid, 0.03 parts of ethylene glycol antimony, and 4 parts of nano-ferrosoferric oxide.
[0069] The preparation method is as in Example 1.
[0070] Example 6
[0071] In this embodiment, a polyester film is provided. The raw materials for preparing the polyester film include the following components in parts by weight: 100 parts of terephthalic acid, 50 parts of ethylene glycol, 1 part of polyether glycol, 1.5 parts of 2,5-tetrahydrofuran dimethanol, 2.5 parts of 2,5-furandicarboxylic acid, 0.03 parts of ethylene glycol antimony, and 4 parts of nano-ferrosoferric oxide.
[0072] The preparation method is as in Example 1.
[0073] The molecular structure diagram of the polyester film provided in this embodiment is as follows Figure 1 shown.
[0074] Comparative Example 1
[0075] In this comparative example, a polyester film is provided. The raw materials for preparing the polyester film include the following components in parts by weight: 100 parts of terephthalic acid, 50 parts of ethylene glycol, 1 part of polyether glycol, 1 part of 2,5-tetrahydrofuran dimethanol, 2 parts of 2,5-furandicarboxylic acid, and 0.03 parts of ethylene glycol antimony.
[0076] The preparation method is as in Example 1.
[0077] Comparative Example 2
[0078] In this comparative example, a polyester film is provided. The raw materials for preparing the polyester film include the following components in parts by weight: 100 parts of terephthalic acid, 50 parts of ethylene glycol, 1 part of polyether glycol, 1 part of 2,5-tetrahydrofuran dimethanol, 0.03 parts of ethylene glycol antimony, and 4 parts of nano-ferrosoferric oxide.
[0079] The preparation method is as in Example 1.
[0080] Comparative Example 3
[0081] In this comparative example, a polyester film is provided. The raw materials for preparing the polyester film include the following components in parts by weight: 100 parts of terephthalic acid, 50 parts of ethylene glycol, 2 parts of 2,5-furandicarboxylic acid, 0.03 parts of ethylene glycol antimony, and 4 parts of nano-ferrosoferric oxide.
[0082] The preparation method is as in Example 1.
[0083] Comparative Example 4
[0084] In this comparative example, a polyester film is provided. The raw materials for preparing the polyester film include the following components in parts by weight: 100 parts of terephthalic acid, 50 parts of ethylene glycol, 0.03 parts of ethylene glycol antimony, and 4 parts of nano-ferrosoferric oxide.
[0085] The preparation method is as in Example 1.
[0086] Comparative Example 5
[0087] In this comparative example, a polyester film is provided. The raw materials for preparing the polyester film include the following components in parts by weight: 100 parts of terephthalic acid, 50 parts of ethylene glycol, and 0.03 parts of ethylene glycol antimony.
[0088] The preparation method is as in Example 1.
[0089] The polyester films provided in the embodiment and the comparative example are respectively placed in a chemical aluminum plating solution (aluminum chloride aqueous solution), and aluminum ions are reduced and deposited on the surfaces of both sides of the polyester film through redox reaction. Then, aluminum is plated by vacuum evaporation, and the aluminum layer is deposited to a thickness of 1 micron (this thickness is the thickness of the aluminum layer on one side) to obtain a composite current collector.
[0090] The structural schematic diagram of the composite current collector provided by the present invention is as follows Figure 2 shown.
[0091] The polyester film and composite current collector provided in the examples and comparative examples were tested for performance, and the test method was as follows:
[0092] (1) Surface energy test: The sample was prepared by the coating method, as follows: First, the polyester film was dissolved in a pre-prepared mixed solution of 1.1.2.2-tetrachloroethane and phenol (mass ratio 1:1) with a concentration of about 5 g / L. The mixed solution was coated on a glass slide with a diameter of 2.5 cm using a rubber-tipped dropper, and the solvent was removed by drying in a vacuum oven at 70°C for 48 hours to obtain a test sample. The contact angles of water and diiodomethane on the test sample were tested by the droplet method using the OCA20 contact angle tester of Dataphysics Company of Germany. The droplet volume was 0.5 μL. The same sample was tested 5 times at different positions and the average value was taken.
[0093] (2) Binding strength test: The composite current collector sample was heat-sealed with EAA and then subjected to a peeling strength test (EAA is propylene ethylene glycol copolymer, which is used as an adhesive to bond the sample to be tested with the peeling test tape. The specific implementation steps can refer to the following national standards). The test standard refers to GB / T25256-2010.
[0094] (3) Conductivity test: The surface resistance of the composite current collector was measured using a four-probe square resistance meter.
[0095] The performance test results are shown in Table 1.
[0096] Table 1
[0097]
[0098] As can be seen from Table 1, the introduction of polar groups does effectively reduce the contact angles of water and diiodomethane on the polyester film surface, indicating that the surface energy of the film can indeed be increased, which is more conducive to the adhesion of aluminum during the aluminum plating process. The subsequent bonding test also confirms this view. The introduction of nano-ferroferric oxide enhances the mechanical interlocking effect of the polyester material and the metal interface and introduces chemical bonding, showing an effective improvement in bonding strength.
[0099] In summary, the composite current collector made of the polyester film provided by the present invention can meet the working and use requirements of lithium-ion batteries, and effectively improves the bonding strength between the polyester film and the aluminum metal coating.
[0100] The applicant declares that the present invention illustrates the polyester film and its preparation method and application through the above-mentioned embodiments, but the present invention is not limited to the above-mentioned embodiments, that is, it does not mean that the present invention must rely on the above-mentioned embodiments to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of the raw materials selected by the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.
Claims
1. A polyester film, characterized in that The raw materials for preparing the polyester film include the following components in parts by weight:
2. The polyester film according to claim 1, characterized in that The ether-containing diol contains at least one ether bond; Preferably, the molecular chain ends of the ether-containing diol are carbon hydroxyl groups; Preferably, the ether-containing diol comprises polyether diol and / or 2,5-tetrahydrofuran dimethanol; Preferably, the polyether diol comprises polytetrahydrofuran.
3. The polyester film according to claim 1 or 2, characterized in that The ether-containing diacid contains at least one ether bond; Preferably, the molecular chain ends of the ether-containing diacid are carboxyl groups; Preferably, the ether-containing diacid comprises 2,5-furandicarboxylic acid.
4. The polyester film according to any one of claims 1 to 3, characterized in that The catalyst includes antimony glycolate.
5. The polyester film according to any one of claims 1 to 4, characterized in that The particle size of the nano-ferroferric oxide is not greater than 200 nm.
6. A method for preparing a polyester film according to any one of claims 1 to 5, characterized in that: The preparation method comprises the following steps: (1) Adding the formulated amount of terephthalic acid, ethylene glycol, ether-containing glycol, ether-containing diacid, catalyst, and nano-ferrosoferric oxide into a reaction kettle, and exhausting nitrogen to remove all air; (2) adding nitrogen until the pressure in the reactor reaches 90-150 kPa; (3) stirring and rapidly heating to 210-230° C. and a pressure of 340-360 kPa; (4) Keep stirring to start the esterification reaction and release the pressure to reduce the pressure to 0 kPa within 110 to 130 minutes; (5) Under the protection of nitrogen atmosphere, stirring and heating to 270-290°C; (6) Using a vacuum pump, the pressure in the reactor reaches -110 to -90 kPa within 50 to 70 minutes; (7) maintaining the vacuum degree until the intrinsic viscosity of the product at the end of the polycondensation is ≥0.7 dL / g, keeping the heating off, stirring, introducing nitrogen to press out the product, and flowing the product into pure water for drawing to obtain a strand; (8) pelletizing and drying the strands, and then biaxially stretching them to form a film; (9) The film is passed through a high-intensity magnetic field and then cooled to obtain the polyester film.
7. The preparation method according to claim 6, characterized in that: The temperature of the purified water in step (7) is 8-12°C; Preferably, the thickness of the film in step (8) is 3 to 10 microns.
8. The preparation method according to claim 6 or 7, characterized in that: The intensity of the high-intensity magnetic field in step (9) is 0.8 to 1.2 T; Preferably, the temperature of the high-intensity magnetic field in step (9) is 40-60° C., and the time of the high-intensity magnetic field is 3-8 minutes.
9. A composite current collector, characterized in that: The composite current collector comprises a base film and aluminum layers disposed on both sides of the base film, wherein the base film comprises the polyester film according to any one of claims 1 to 5; Preferably, the thickness of the aluminum layer is 0.5 to 1.5 microns.
10. A method for preparing the composite current collector according to claim 9, characterized in that: The preparation method comprises the following steps: The polyester film is placed in a chemical aluminum plating solution, aluminum ions are reduced through redox reaction and deposited on the surfaces of both sides of the polyester film, and then aluminum is plated through vacuum evaporation to obtain the composite current collector.
Citation Information
Cited By
Preparation method of polyarylester composite film with double metal-plated surfaces and polyarylester composite film
CN121927454A